A Variable Neighborhood Search-Based Heuristic for the Multi-Depot Vehicle Routing Problem - Arif Imran (Institute of Research and Community Outreach - Petra Christian University, 2013)
The multi-depot vehicle routing problem (MDVRP) is addressed using an adaptation of the variable neighborhood search (VNS). The proposed VNS algorithm besides using several neighborhoods and a number of local searches has a number of additional features. These include a scheme for identifying borderline customers, a diversivication procedure and a mechanism that aggregates and disaggregates routes between depots. The proposed algorithm is tested on the data instances from the literature and produces competitive results.